Impact of buffer salts on protein-protein-adsorber interactions by using E. coli host proteins in ion exchange frontal chromatography - Jana Otte (2019)
This master thesis investigated the impact of buffer salts on protein-protein-adsorber interactions in ion exchange chromatography. Six buffers with different properties were chosen as well as two proteins, lysozyme and BSA, which are different in size and charge. To relate to practice, host cell proteins from E. coli were used. For the determination of the binding behaviour, the zonal and frontal chromatographic method were applied. During the zonal chromatography it could be observed that through protein-protein interactions, proteins were adsorbed which carried the same charge as the stationary phase. The received breakthrough curves from frontal chromatography gave information about the dynamic and static binding capacity. Further the dependency of the charge and ionic strength of each buffer on the binding capacities were investigated. To this end, the molarity and the pH was adjusted. Significant differences in the DBC value for each protein solution could be observed. The results showed that the assumptions found in literature [Herrmann, 2002] can´t be applied directly and that more parameters need to be considered individual. In this process several proposals from different sources of literature were applied regarding protein interactions [Rösch et al, 2016], zeta potential [Burns et al., 1999], ionic strength [Salgin et al., 2012] and the influence of the pH [Shi et al, 2005]. It was revealed that the protein size and the formation of protein complexes have a great impact on the breakthrough curve. Through different types and concentrations of buffer salts and changes of the pH, the protein adsorption and therefore the form of the breakthrough curve can be influenced. This impact is reflected rather in the dynamic binding capacity than in the static binding capacity. The results also revealed that it is from advantage to use salt ions which carry the same charge as the desired protein to achieve a higher dynamic binding capacity. Concerning the buffer salt concentration, not only a too high buffer salt concentration (50 mM) led to a decrease of the dynamic binding capacity but also a too low concentration (10 mM). Regarding the pH, the change of the pH from 6.5 to 7.5 enhanced the interaction between BSA and lysozyme (expressed through an increased dynamic binding capacity) because of the more negative net charge of BSA. Especially the protein interactions would make it more difficult to isolate one protein from a protein mixture.